3D models of the hematopoietic stem cell niche under steady-state and active conditions - Lisa Rödling (Nature Portfolio, 2017)
Abstract Hematopoietic stem cells (HSCs) in the bone marrow are able to differentiate into all types of blood cells and supply the organism each day with billions of fresh cells. They are applied to cure hematological diseases such as leukemia. The clinical need for HSCs is high and there is a demand for being able to control and multiply HSCs in vitro. The hematopoietic system is highly proliferative and thus sensitive to anti-proliferative drugs such as chemotherapeutics. For many of these drugs suppression of the hematopoietic system is the dose-limiting toxicity. Therefore, biomimetic 3D models of the HSC niche that allow to control HSC behavior in vitro and to test drugs in a human setting are relevant for the clinics and pharmacology. Here, we describe a perfused 3D bone marrow analog that allows mimicking the HSC niche under steady-state and activated conditions that favor either HSC maintenance or differentiation, respectively, and allows for drug testing.